2012
DOI: 10.1007/s10147-012-0375-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of S-1 with concurrent radiotherapy in patients with locally recurrent rectal cancer

Abstract: This phase I trial of S-1 chemotherapy with pelvic radiotherapy for locally recurrent rectal cancer revealed that the MTD for S-1 was 70 mg/m(2)/day and the RD was 60 mg/m(2)/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…the radiotherapy regimen included s-1 (taiho Pharmaceutical Co, tokyo, Japan) as a radiosensitizer from day 1 to day 10, with an s-1 dose of 60 mg/m 2 /day; s-1 has been shown to be a radiosensitizer. [13][14][15][16] the detailed protocol for the radiotherapy regimen applied in this study has been described previously. 17 the target interval between the completion of radiotherapy and surgery was 4 weeks.…”
Section: Short-course Chemoradiotherapy With Delayed Surgerymentioning
confidence: 99%
“…the radiotherapy regimen included s-1 (taiho Pharmaceutical Co, tokyo, Japan) as a radiosensitizer from day 1 to day 10, with an s-1 dose of 60 mg/m 2 /day; s-1 has been shown to be a radiosensitizer. [13][14][15][16] the detailed protocol for the radiotherapy regimen applied in this study has been described previously. 17 the target interval between the completion of radiotherapy and surgery was 4 weeks.…”
Section: Short-course Chemoradiotherapy With Delayed Surgerymentioning
confidence: 99%
“…DLTs included grade 3 anorexia, nausea, fatigue and leucopenia. S-1-based chemoradiotherapy has been proven to be safe and effective in some malignancies, and the recommended dose of S-1 is usually 60-80 mg/m 2 daily based on several phase I studies [21][22][23][24]. In this dose-escalation study, the MTD of S-1 was determined to be 70 mg/m 2 daily.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated that NA-CRT combined with S-1 is associated with mild toxicity and exhibits an efficacy equivalent to that of other CRT regimens used for RC (8)(9)(10)(11)(12). Clinical studies of irinotecan (CPT-11) plus S-1 combination therapy have been reported to produce non-inferiority outcomes for metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%